Villous Capillary Lesions Of Placenta: A Ten-Year Experience With Brief Review Of Literature - Manickam, Niraimathi; G’boy Varghese, Renu; Pansalkar, Manjiri; Ramdas, Anita; Daniel, Mary (Annals of Pathology and Laboratory Medicine, 2018)
Background: Villous capillary (VC) lesions of placenta range from reactive to benign tumors such as chorangiosis (CH), chorangiomatosis (CM) and chorangioma (CA). Associated with perinatal morbidity and mortality, these rare lesions are documented with maternal, placental and fetal risk factors. The aim of this study was to analyze the clinico-pathological profile of VC lesions of placenta and to compare the associated risk factors between VC lesion (CH) and those with no VC lesions. Methods: This retrospective study includes all the VC lesions of Placenta diagnosed in Pondicherry Institute of medical sciences from January 2006 to February 2016. For comparison, gestational age matched controls with no VC lesions were obtained. Chi-square test or fischer’s exact test was used for statistical analysis. Results: Of 29 VC lesions of placenta (5.6%) in 10 years, 27 were CH. Commonly associated feto-maternal factors include anemia (47.4%), oligohydramnia (33.3%), infection (28.6%), pre-eclampsia (23.8%), NICU admission (47.8%), fetal growth retardation (17.4%), congenital anomaly (17.4%), intrauterine death (13%). When compared with controls, CH had significantly increased LSCS, premature rupture of membranes and histologically, chorioamnionitis and funisitis that support its infective etiology. One case of CA associated with IUGR, polyhydramnios was found to have CH in her next pregnancy which points to a possibility of genetic predisposition among VC lesions. CM was diagnosed in primi with severe pre-eclampsia and asymmetric IUGR. Conclusion: Prevalence of CH is 5.2%. VC lesions of placenta are commonly associated with complicated pregnancy and neonatal morbidity.